If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + 6x = 18 Solving -12 + 6x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 6x = 18 + 12 Combine like terms: -12 + 12 = 0 0 + 6x = 18 + 12 6x = 18 + 12 Combine like terms: 18 + 12 = 30 6x = 30 Divide each side by '6'. x = 5 Simplifying x = 5
| 6+2x-3=9x+15-5x | | 6+(-2)+(-9)= | | y-1=-2/3(x+2) | | 4(2x+6)-3x=9 | | 9-10p=1 | | (20-4)*2+3= | | 16x/8x | | 6y+11y=68 | | -x-1=-2x+2 | | 21+3x=9-3x | | z/3=-18 | | 3(2x+6)=54 | | -2b+5+5b=20 | | 5(10y+8)-4(7y+9)= | | 10x+6y-3=0 | | -11x^2-2x-6=0 | | 9/3-2= | | 6n-8=2(2n+1) | | -8(2b+1)+(17b-2)=0 | | 320(t)=-16t^2+190t+20 | | 3+12a+3*4a-2+4b+7b*4/2 | | -4(5-y)=20 | | 14(5-y)=20 | | x^2(5x-1/4)(2x+1/4) | | 1.7q-1.6-5.9q=5.2q-4.1 | | -3(2x-6)-4x+9= | | 7y+1=8y+5 | | x^2-x+64=0 | | 6x^2+12x+c=0 | | 8x+17=5x+35 | | x^2+4x+48=0 | | 8/x-5x=4 |